Emotions In The Qur'an: A Thematic Study of Verses on Self-Control: (Emosi Dalam Al-Qur’an: Kajian Tematik Terhadap Ayat-Ayat Pengendalian Diri) - Nurlaila, Siti; Alif, Muhammad (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
Uncontrolled emotions often trigger a variety of psychological and social problems, such as impulsive behavior, conflict, anxiety, and spiritual imbalances. However, the majority of research to date has used a descriptive-normative approach and has not yet developed a model of emotional regulation based on the Qur'an. This research aims to fill that gap by analyzing the Qur’an’s verses that reflect basic human emotions, especially in terms of self-control strategies. A qualitative approach based on literature review and thematic interpretation (mawdu'i) is used, namely by grouping verses scattered in various surahs into the theme of emotion and self-control. The data was analyzed through theory-based coding techniques based on the development of a conceptual framework of self-control according to the Qur'an. The results of the study state that the Qur'an not only acknowledges the existence of human emotions and desires, but also provides moral and spiritual guidance in managing them constructively. These values enrich the thematic discourse of Islamic interpretation and psychology, particularly in building the foundation of spiritual regulation to respond to modern psychiatric and social challenges. The research offers novelty by bridging thematic tafsir and grounded theoretical approaches to construct an emotion regulation model directly from revelation.  Additionally, this study produces an e-book intented for academics, educators, and practitioners of Islamic counseling. It further recommends multidisciplinary research to integrate the Qur’anic concept of self-control into educational curricula, therapeutic models, and faith-based counseling frameworks.